2022
DOI: 10.1021/acs.energyfuels.2c00707
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Sulfation of CaO and CaCO3 in Eutectic CaF2–CaCl2

Abstract: To achieve deep cuts in greenhouse gas emissions from stationary point sources such as carbon intensive industry and fossil power generation, carbon capture and storage (CCS) will be a necessity. Carbon capture in molten salts (CCMS) is an emerging technology with high potential. In CCMS, the reversible reaction between calcium oxide (CaO) and carbon dioxide (CO 2 ) to form calcium carbonate (CaCO 3 ) is utilized, with the active substances being dissolved or partly dissolved in molten salts. CCMS has previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is a thermal swing process where the absorption is performed at 650-830 °C and desorption at 950 °C (ambient pressure) when using CaO in a eutectic CaCl 2 -CaF 2 melt (86.2 : 13.8 wt%). 13 Previous CCMS research has focused on proof-of-concept work where it was found that CCMS is capable of capturing CO 2 , [14][15][16][17][18] and up to 85 % of the CaO is converted at multicycle absorption. 13 The next step for the technology development is to perform a techno-economic evaluation to explore the feasibility for upscaling.…”
Section: Introductionmentioning
confidence: 99%
“…It is a thermal swing process where the absorption is performed at 650-830 °C and desorption at 950 °C (ambient pressure) when using CaO in a eutectic CaCl 2 -CaF 2 melt (86.2 : 13.8 wt%). 13 Previous CCMS research has focused on proof-of-concept work where it was found that CCMS is capable of capturing CO 2 , [14][15][16][17][18] and up to 85 % of the CaO is converted at multicycle absorption. 13 The next step for the technology development is to perform a techno-economic evaluation to explore the feasibility for upscaling.…”
Section: Introductionmentioning
confidence: 99%